La didáctica en el proceso de enseñanza aprendizaje con necesidades educativas especiales en la Unidad Educativa Nicolás Guillén. - López Noroña, Carina Mariela (2021)
The present investigation "Didactics in the teaching-learning process with special educational needs in the Nicolás Guillén Educational Unit ”has raised as the main objective, to strengthen the teaching-learning process of students with special educational needs in the "Unidad Educativa Nicolás Guillén ”in the 2020-2021 school year; the methodology has a quantitative approach, since the deductive method based on the existing theory has been used, at the same time has worked with two variables: didactics and special educational needs, the same that have a cause and effect relationship, which led to systematize the proposal which consists of the creation of methodological guides for the teaching process learning in boys and girls with special educational needs. In the same way It has been concluded that from the initial diagnosis it was possible to show that the teachers do not know of methodological strategies to attend to children with stupidity special educational. Subsequently, the development and application of the proposal based in methodological strategies has allowed to strengthen the teaching-learning process in students, implementing methodological strategies suitable for each style and necessity of life, in order to help in their learning and development, making the teacher is more inclusive, personalized and empathetic in their teaching work.